Thermal Imaging Following Exercise in Working Dogs - Farley, Calan M.; Kaynaroglu, Patricia; Magness, Donna; Riegel, Ronald J.; Otto, Cynthia M. (Frontiers in Veterinary Science, 2021)
Disaster search dogs traverse diverse and unstable surfaces found in collapsed buildings. It is unknown if the physical conditioning on a treadmill involves the same muscle groups that are involved in rubble search. This 14-week prospective cohort study was conducted to investigate changes within the thermal gradients of specific dog muscles following treadmill compared to rubble search. Nine dogs, ranging in age from 6 months to 4 years, were randomly assigned to one of two groups. Each week the two groups would participate in either 20 minutes of treadmill or rubble searches. Prior to exercise, the dogs were weighed and then kenneled in a temperature-controlled study room for 20 minutes at 21°C. Pre-exercise thermal images were then captured of the standing dog from the dorsal, left and right lateral, and caudal perspectives, and of the sitting dog from the rostral perspective. Following a 10-minute warm-up period of stretches, dogs proceeded to either treadmill or search. Upon completion, dogs were kenneled in the study room for 20 minutes prior to post-exercise thermal images. Images were sectioned into 22 muscle regions, the pre-exercise images were subtracted from the post-exercise images to determine the temperature difference (ΔT) for that dog, on that day, for that activity. Thermography measures radiant energy, temperature, and converts this information into an image. This study looked at ΔT within a region pre and post exercise. The study failed to find a statistically significant difference in the ΔT within each muscle group between treadmill and search activities. There was a decrease in ΔT within all muscle regions over the of the study except for the right cranial shoulder, right caudal shoulder, and right hamstring for the treadmill activity only. The decrease was significant in the pelvis, left longissimus, right cranial shoulder for the search activity, left oblique, left caudal shoulder, and left quadricep muscular regions. These findings suggest that ΔT in muscle groups are similar between treadmill exercise and rubble search. Regardless of the exercise type, 14 weeks of structured Search and Rescue training and treadmill exercise resulted in less ΔT associated with a structured weekly exercise.